FREQUENCY AND SEVERITY OF STEATOSIS IN PATIENTS WITH CHRONIC HEPATITIS-C - Khan, Adil Naseer; Said, Khalid; Ali, Kishwar; Latif, Humera; Gul, Rahid (Journal of Ayub Medical College Abbottabad, 2015)
Background: Hepatitis-C viral infection is a global health problem. It has been estimated that approximately 170 million individuals are infected with hepatitis-C virus. Hepatic steatosis is a frequent histological feature in patients with chronic hepatitis-C infection. Histological examinations show that up to 50% of these patients have variable degrees of hepatic steatosis, even in the absence of other possible steatogenic factors like alcohol, drugs or metabolic syndromes. The objective of this study was to determine the frequency and severity of steatosis in patients with Chronic Hepatitis-C. Methods: This cross sectional study was carried out from 1st January 2010 to 1st July 2010 at the department of Gastroenterology PIMS, Islamabad. A total of 127 patients of chronic hepatitis-C were enrolled in the study after taking informed written consent. Frequency and severity (mild, moderate and severe) of steatosis was assessed on the basis of liver biopsy. Results: A total of 127 patients were included in the study. Mean age of the patients was 36.24 years. Out of 127 patients, 48(38%) were male and 79(62%) were female. Steatosis was present in 50(39%) patients with chronic hepatitis-C infection. whereas steatosis was absent in 77(61%) patients. Conclusion: The presence of steatosis on liver biopsy in patients with chronic hepatitis-C is common (39% patients) and female patients had slightly more severe degree of steatosis as compared to male patients. Keywords: Chronic hepatitis-C, Steatosis, Frequency, Severity